ROLE OF MUSHROOMS AS NUTRACEUTICAL AN OVERVIEW - SIKHA DUTTA (International Journal of Pharma and Bio Sciences, 2013)
Literally the term ‘Nutraceutical’ is a conjunction of nutrition and pharmaceuticals. In fact Nutraceutical are the natural substances or food supplements that claim to have medicinal effects on human health. The International medical boards and community medicines has described the term Nutraceutical as any substance which may be considered as food or a part of food and provides some medical or health benefits including prevention, treatment and cure of some diseases (Barros et al., 2008). It is needless to say that a bulk of our present population relies on drug resources of plant origin and the herbal medicines are increasingly being used not only by developing countries but also by the developed countries as supplement or alternative to their health care system. Preparation of drugs and medicines from natural resources is the most eco-friendly method of new drug discovery Rajeshkumar et al., (2012); Kyung et al., (2005). Considering the growing demand of herbal medicines, the fast growing mushrooms have received remarkable interest in recent decades with realization to the fact that they are good sources of delicious food with high nutritional attributes and some having medicinal values as well. Mushrooms are nutritionally functional food and a source of medicines and most remarkably can produce mycopharmaceuticals and mycoNutraceutical (Chang, 1996; Chang and Miles, 1993). Many edible mushrooms like Pleurotus sp., Agaricus bisporus, Agaricus campestris, Volvariella volvacea, Lentinus edodes, Grifola sp., Schizophyllum communis, Auricularia auriculata etc. enjoy a high demand of premium price because of their high nutritional value as well as their pharmaceutical potential. Keeping this fact in mind, the present topic, ‘Role of Mushrooms as ‘Nutraceutical’ has been chosen giving emphasis on the pharmaceutical properties of some edible mushrooms which can safely be used as Nutraceutical.